Tourist satisfaction and destination loyalty intention: A structural and categorical analysis - Patrícia Oom do Valle; Jo\~ao Albino Silva; Júlio Mendes; Manuela Guerreiro (International Journal of Business Science & Applied Management (IJBSAM), 2006)
This study explores the relationship between travel satisfaction and destination loyalty intention. The research was conducted with 486 tourists visiting Arade, a Portuguese tourist destination. Taking as the basis the use of structural equation modelling (SEM), the results substantiate the importance of tourism satisfaction as a determinant of destination loyalty. Also, a categorical principal components analysis (CATPCA) provides a detailed analysis of this cause-effect relationship by establishing that greater levels of satisfaction (measured by overall satisfaction in terms of holiday experience, destination attributes and met expectations) result in increased likelihood of future repeat visits and a keen willingness to recommend the destination to others. Clusters of tourists were also identified and characterized in relation to satisfaction levels and loyalty intentions. These analyses provide a useful background in the planning of future tourist marketing strategies.
Keywords: 650; Itourism; satisfaction; loyalty; SEM; CATPCA; clusters